KERAGAMAN FENOTIPE DAN PRODUKTIVITAS LABU KUNING NUSANTARA (Cucurbita moschene Dutchene) DALAM RANGKA PENGEMBANGAN VARIETAS UNGGUL - Reza Prakoso Dwi Julianto; Astri Sumiati (BUANA SAINS, 2017)
The increase of population and the depletion of productive agricultural land causes the availability of rice as the staple food as carbohidrat becomes unbalanced. Efforts to reduce dependence on rice should be made, through the diversification of alternative food crops containing high carbohydrates. Pumpkin plants (waluh) is one of the crop that have high carbohydrate content and has many types. This research aims to collect various types of yellow squash varieties as the initial material in the assembling of superior varieties, and to identify vegetative character and agronomic character of yellow squash pumpkin varieties. The research was conducted in Randuagung Village, Lumajang Regency with height of 112 asl. The materials used in are local lumajang pumpkin seeds and local poor pumpkin. The results of this study indicate that the ratio of male flowers and female flowers on both varieties of local yellow squash showed the number of male flowers more than the number of female flowers. The beta-carotene content of local lumajang is lower than the local yellow squash is seen from the color of the pumpkin the yellow is getting faded and the taste is less sweet. The resistance to the disease of both varieties of local yellow squash indicates the tolerance criteria. The male juvenile blueberry male jungle flowers are faster than the local yellow squash lumajang, but the age of the local pumpkin flower lumajang is faster than the local yellow squash.The yellow local pumpum lumajang color is relatively the same that is brown, while the varieties of local yellow pumpkin there is a difference that is brown and green.